The experience of women with an eating disorder in the perinatal period: a meta-ethnographic study - Sarah Fogarty; Rakime Elmir; Phillipa Hay; Virginia Schmied (BMC, 2018)
Abstract Background Pregnancy is a time of enormous body transformation. For those with an eating disorder during pregnancy this time of transformation can be distressing and damaging to both the mother and the child. In this meta-ethnographic study, we aimed to examine the experiences of women with an Eating Disorder in the perinatal period; that is during pregnancy and two years following birth. Method A meta-ethnographic framework was used in this review. After a systematic online search of the literature using the keywords such as pregnancy, eating disorders, anorexia, bulimia, binge eating disorder, perinatal, postnatal and post-partum, 11 papers, involving 94 women, were included in the review. Results A qualitative synthesis of the papers identified 2 key themes. The key theme that emerged during pregnancy was: navigating a 'new' eating disorder. The key that emerged in the perinatal period was return to the 'old' eating disorder. Conclusion Following a tumultuous pregnancy experience, many described returning to their pre-pregnancy eating behaviors and thoughts. These experiences highlight the emotional difficulty experienced having an eating disorder whilst pregnant but they also point to opportunities for intervention and a continued acceptance of body image changes. More research is needed on the experiences of targeted treatment interventions specific for pregnant and postpartum women with an eating disorder and the effectiveness of putative treatment interventions during this period.